Cryostorage to what end?: Autologous stem cell products in Burkitt lymphoma, acute lymphoblastic leukemia, acute myeloid leukemia, and myeloproliferative neoplasm patients - Kriegsmann, Katharina; Pavel, Petra; Bochtler, Tilmann; Schmitt, Anita; Sauer, Sandra; Kriegsmann, Mark; Bruckner, Thomas; Klein, Stefan; Klüter, Harald; Müller-Tidow, Carsten; Wuchter, Patrick (Transfusion medicine and hemotherapy, 2021)
Introduction: Recently, we identified a huge discrepancy between the collection practice and the actual utilization of cryopreserved peripheral blood stem cells (PBSCs) for high-dose chemotherapy (HDCT) and autologous blood stem cell transplantation (ABSCT). Specifically, patients with Burkitt lymphoma, acute leukemia, and myeloproliferative neoplasms (MPN) were frequently not referred for ABSCT after successful PBSC collection. Objective: The aim of this study was to identify variables that are associated with the non-utilization of PBSC grafts. Methods: We retrospectively analyzed the collection, storage, and disposal of PBSC grafts in Burkitt lymphoma (n = 18), acute lymphoblastic leukemia (ALL, n = 22), MPN (n = 18), and acute myeloid leukemia (AML, n = 71) patients. Patients who underwent autologous PBSC collection at 2 collection and transplantation centers between 2001 and 2012 were included and followed up until 2016. Results: None of the Burkitt lymphoma patients were referred for ABSCT. Only in 1 (6%) patient, the graft was discarded after the patient’s death. In all other patients (n = 17, 94%), the grafts were stored independently of the patient’s status (death, n = 4, 22%; no follow-up, n = 6, 33%; no indication for ABSCT given, n = 7, 39%). In ALL patients, 4 (18%) patients underwent ABSCT after a median follow-up of 74 (1-182) months. In the remaining patients, PBSC grafts were either discarded (8 patients, 36%) or stored until the reference date (10 patients, 45%). Seven of 18 MPN patients (39%) underwent ABSCT. ABSCT was performed in 24 (34%) AML patients. In 20 (28%) patients who were not referred to ABSCT, an allogeneic transplantation (TPL) was performed. Fifteen (21%) patients received palliative care or deceased, and their grafts were discarded in all but 1 patient. Additional grafts were discarded in 21 (31%) patients and stored in 9 (13%) patients who underwent ABSCT or allogeneic TPL (n = 44). Conclusions: As the role and efficacy of autologous HDCT/ABSCT are not established in the analyzed entities, the indication for PBSC collection should be reanalyzed in regular intervals. Moreover, PBSC grafts from patients who have deceased, have insufficient grafts, or have already undergone an allogeneic TPL should be considered for disposal or (if applicable) for research use, to economize storage costs on a rational basis.